PENGARUH TEKNIK JIGSAW ACTIVITIES TERHADAP HASIL KEMAMPUAN BERBICARA AKADEMIK MAHASISWA PRODI B.INGGRIS UNSIKA - Puspitaloka, Nina; Srisudarso, Mansur (Majalah Ilmiah SOLUSI, 2015)
Teachers often face the problem of having lack creativity regarding the innovative teaching technique in speaking. Therefore the research was aimed to know the effect of jigsaw activities technique on the student’s performance of English Speaking Skill. The quantitative research was to measure the pertaining effects of jigsaw activities on the speaking performance. The data was taken from an experimental research, involving 210 students in UNSIKA in the English Education program. The 2nd semester students were randomly selected. 35 students run learning activity with jigsaw activities technique and 35 students studied in control group. The experimental group got particular treatments related to jigsaw activities technique. The treatment for the experimental group was to improve their speaking skill. The control group was taught in conventional teaching technique. Both groups pre-test and post-test to identify their performance on the speaking skill improvement. The measurement for both groups was conducted at the same test. In term of quantitative approach, quasi experiment design was used to describe the different result of experimental group and control group. T-test was used to analyze the data to measure the effect of jigsaw activities technique in comparison to conventional teaching technique. By means of the T-test, the finding showed that jigsaw activities affected performance of English speaking skill. It is recommended for English teacher to use jigsaw activities as alternative to improve quality of teaching.